Endocan in Cancers: A Lesson from a Circulating Dermatan Sulfate Proteoglycan - Maryse Delehedde; Lucie Devenyns; Claude-Alain Maurage; Romain R. Vivès (International Journal of Cell Biology)
As most proteoglycans exert their biological activities in the pericellular region, circulating Endocan has appeared since its discovery as an atypical dermatan sulfate proteoglycan, with distinctive structural and functional properties. Endocan is naturally expressed by endothelial cells, highly regulated in presence of proinflammatory and proangiogenic molecules, binds to matrix proteins, growth factors, integrin, and cells, and may be then considered as an accurate marker of endothelial activation. Consequently, Endocan expression has been associated with a growing number of pathological conditions where endothelium gets challenged and notably in highly vascularized cancers. In this context, Endocan has indeed been rapidly emerging as a promising tissue- and blood-based marker of the vascular growth and neoangiogenesis during cancer progression. Furthermore, very recent studies have reported an expression of Endocan by the tumor cells themselves. This highlights Endocan as a multifaceted molecule with a great interest for researchers and clinicians to better understand tumor development, from the bench to the clinics. With promising perspectives of clinical applications, Endocan thus appears as an exciting model for on going and future developments of proteoglycan-based approaches in cancer diagnostics and/or therapy.